More deadly than the male : masterpieces from the queens of horror - Davis, Graeme, 1965-; Shelley, Mary Wollstonecraft, 1797-1851; Hall, S. C., Mrs., 1800-1881; Gaskell, Elizabeth Cleghorn, 1810-1865; Trevanion, Ada; Edwards, Amelia B., 1831-1892; Alcott, Louisa May, 1832-1888; Stowe, Harriet Beecher, 1811-1896; Phelps, Elizabeth Stuart, 1844-1911; Braddon, M. E. (Mary Elizabeth), 1835-1915; Linton, E. Lynn (Elizabeth Lynn), 1822-1898 (Pegasus Books, 2019)
A darkly luminous new anthology collecting the most terrifying horror stories by renowned female authors, presenting anew these forgotten classics to the modern reader.--